Pemanfaatan e-tikbroh.yak: aplikasi jemput antar sampah non-organik rumah tangga di Kota Banda Aceh (Making use of e-tikbroh.yak: the pick-up and delivery non-organic waste service app in Banda Aceh) - Rosemary, Rizanna; Syam, Hamdani M; Fadlia, Faradilla; Nisa, Uswatun (Universitas Syiah Kuala, 2023)
In an endeavor to assist the Banda Aceh City Government in effective waste management, a group of lecturers and students from Syiah Kuala University (USK) has introduced an innovative waste management solution in the form of a digital-based waste collection and disposal application named e-tikbroh.yak. This application is designed to pick up pre-sorted waste from users, including individuals and communities, and then distribute the segregated waste to collectors and partners who have ordered or purchased it for various productive purposes. The distribution of this application to the community is considered essential as it streamlines the waste management process by promoting waste sorting and implementing the 3 R (Reduce-Reuse-Recycle) waste management concept, thereby fostering a conscious approach to waste management. Furthermore, e-tikbroh.yak creates new employment opportunities within the community, both as application couriers and by generating additional income through the collection of sorted waste. To expand its reach and accessibility, the e-tikbroh.yak application will soon be made available on the Play Store and web browsers for non-Android smartphone users in Banda Aceh City. Following its public introduction, a Users Acceptance Test (UAT) was conducted to ensure the effective and optimal functioning of the application system. This paper aims to elucidate two key aspects: 1) introducing e-tikbroh.yak to the community and partners, and 2) assessing the application's performance through the User Acceptance Test (UAT) procedure. The outcome of the UAT demonstrated that the people of Banda Aceh City found the application's operation to be smooth and user-friendly.